2010
DOI: 10.1002/cbdv.200900091
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Antimicrobial Activity of the Essential Oils from Several Hypericum Taxa (Guttiferae) Growing in Central Italy (Appennino Umbro‐Marchigiano)

Abstract: The chemical composition of the essential oils of nine taxa from seven sections of Hypericum L. (Guttiferae; H. perforatum subsp. perforatum, H. perforatum subsp. veronense, H. calycinum, H. montanum, H. richeri subsp. richeri, H. hyssopifolium, H. hirsutum, H. hircinum subsp. majus, and H. tetrapterum) occurring in central Italy (Appennino Umbro-Marchigiano) was analyzed by GC/FID and GC/MS. A total of 186 compounds were identified in the different species and subspecies, accounting for 86.9-92.8% of the tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 16 publications
2
21
0
1
Order By: Relevance
“…In agreement to our results, ˛-pinene was also previously reported as a major component of St. John's wort essential oil (Akhbari et al, 2012;Chauhan et al, 2011;Helmja et al, 2011;Saroglou et al, 2007;Pavlovic et al, 2006;Baser et al, 2002;Erken et al, 2001;Cakir et al, 1997). Contrarily, compounds such as germacrene D (Helmja et al, 2011;Maggi et al, 2010;Saroglou et al, 2007), 2-methyl-n-octane (Helmja et al, 2011;Pavlovic et al, 2006), -muurolene (Pavlovic et al, 2006) and carvacrol (Erken et al, 2001), which have been previously reported as main components of H. perforatum essential oils, were not detected at all in the investigated samples.…”
Section: Chemical Profiles Of Essential Oilssupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement to our results, ˛-pinene was also previously reported as a major component of St. John's wort essential oil (Akhbari et al, 2012;Chauhan et al, 2011;Helmja et al, 2011;Saroglou et al, 2007;Pavlovic et al, 2006;Baser et al, 2002;Erken et al, 2001;Cakir et al, 1997). Contrarily, compounds such as germacrene D (Helmja et al, 2011;Maggi et al, 2010;Saroglou et al, 2007), 2-methyl-n-octane (Helmja et al, 2011;Pavlovic et al, 2006), -muurolene (Pavlovic et al, 2006) and carvacrol (Erken et al, 2001), which have been previously reported as main components of H. perforatum essential oils, were not detected at all in the investigated samples.…”
Section: Chemical Profiles Of Essential Oilssupporting
confidence: 92%
“…Sesquiterpene hydrocarbons represented the major fraction in the oils from Nor (51.7%), Galogah (32.75%), Darrod (21.6%), Lahijan (35.5%) and Mashhad (31.4 %). Similar results were reported for H. perforatum growing in Italy and France (Maggi et al, 2010;Schwob et al, 2002). On the other hand, monoterpene hydrocarbons were the major fraction in the essential oils from Kharw (38.8%), Toskestan (25.3%) and Tonekabon (25.6%), as well as alkanes, which are dominant in few Hypericum species, constituted the major fraction in the samples from Azadshahr (53.7%) and Javaherdeh (34.8%).…”
Section: Chemical Profiles Of Essential Oilssupporting
confidence: 83%
“…Some authors stated different chemical compositions of H. perforatum essential oils depending on the plant organs examined (leaves, flowers, stems) [28,41]. Moreover, the differences in the composition of essential oils may originate from different varieties within the same species [27], and as in most papers this taxonomic category was not given, the comparison of essential oils becomes more difficult. Generally speaking, there are H. perforatum essential oils with sesquiterpenoids as dominant compound class [20-21, 27, 39], but there are also oil samples where alkanes [23,29] or monoterpene hydrocarbons [33,40] were the major classes of compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, leaves and flowers of H. caprifoliatum vary in the nonane and b-caryophyllene concentrations (Ferraz et al 2005a). d-Selinene was the most represented compound of essential oils isolated from flowers of H. hircinum (Maggi et al 2010).…”
Section: Chemical Composition Of Hypericum Essential Oilsmentioning
confidence: 99%